2020
DOI: 10.3390/biomedicines8020039
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Microbiota Bioactivity and Bioavailability of Functional Compounds: A Mini-Review

Abstract: Numerous studies have demonstrated the role of the microbiota in supporting the physiological functions, owing to its metabolomic component. The presence of biocomponents generally leads to the correction of the microbial pattern correlated with the reduction of oxidative pressure. This study aims to present the main processes that correlate the bioavailability and bioactivity of some functional components through the action of the human microbiota. The use of probiotics and prebiotics is an innovative manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 93 publications
(108 reference statements)
1
45
0
2
Order By: Relevance
“…Phytocomplexes can be metabolized by the microbiota, but they can also modulate it, in order to improve their role in the prevention and amelioration of several diseases [75]. Moreover, the presence of several classes of compounds identified in all the extracts tested underlines the need to further analyze the effects of their single bioactive components.…”
Section: Discussionmentioning
confidence: 99%
“…Phytocomplexes can be metabolized by the microbiota, but they can also modulate it, in order to improve their role in the prevention and amelioration of several diseases [75]. Moreover, the presence of several classes of compounds identified in all the extracts tested underlines the need to further analyze the effects of their single bioactive components.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is reported that natural products could have a xenobiotic effect, and the intestinal ecosystem has been shown to be responsible for xenobiotic biotransformation [40]. Recent studies displayed that polysaccharides could reduce oxidative stress by regulating gut microbiota composition or activating gastrointestinal immune cells, and could be degraded in gastrointestinal tract, thus they could pass through the intestinal epithelial cells and enter the blood circulation [6].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to unravel the molecular mechanism underlying C. coli-host interactions in more detail. Given the importance of the gut luminal milieu and its metabolomic features that are determined by the gut microbiota composition, in contributing to "intestinal health" [45], we are currently assessing the immunomodulatory (i.e., anti-oxidative, anti-inflammatory) properties of distinct probiotic and prebiotic compounds as therapeutic and/or preventive strategies to combat Campylobacter induced inflammatory responses in the vertebrate host with intestinal inflammatory comorbidities.…”
Section: Discussionmentioning
confidence: 99%